Obfuscation in competitive markets - Ernst Fehr; Keyu Wu (University of Zurich, Department of Economics, 2021)
In many markets, firms make their products complex through add-ons, thus making them difficult to evaluate and compare. How does this product obfuscation affect competition, sellers' profits, and buyers' welfare? We study these questions in a competitive experimental market in which sellers have the opportunity to obfuscate by add-on features, and buyers endogenously decide how much time to spend on searching for the best product. We show that stable obfuscation levels emerge that reduce buyers' welfare by ensuring that total prices are substantially above marginal cost and by inducing buyers to make mistakes and to waste their time searching. Competition operates through lowering salient headline prices, but sellers are able to appropriate a considerable share of the surplus with expensive add-on features. In contrast, prices quickly converge to marginal cost if we remove obfuscation opportunities. We thus provide direct causal evidence that obfuscation mitigates competition and generates positive profits because buyers typically search only a small share of the product space. Our results also suggest that purely exploitative obfuscation tends to be much less stable than obfuscation by surplus-enhancing add-on features because buyers' aversion to complicated products may have a non-negligible impact on sellers' obfuscation decisions.
Keywords: 330; Produktgestaltung; Produktdifferenzierung; Preismanagement; Wohlfahrtsanalyse; Theorie